Success and chance in Dutch art literature (1604-1752) - Kolfin, Elmer 1969- (2022)
The idea that chance plays a role in a person’s life seems trivial nowadays. Yet early-modern Dutch writers on the lives of painters did not see it this way at all. Despite all the attention that recent socioeconomic art historiography has paid to routes to success, the structural focus of early-modern writers on the role played by chance in the pursuit of painterly success has not previously been noted. The painter-authors Karel van Mander, Samuel van Hoogstraten, Arnold Houbraken and Johan van Gool, whose texts are analysed in this article, reveal that chance was perceived as a dominant force that artists had either to exploit or to resist. This article discusses which instruments these practical men believed were available to artists. It shows how and why faith in the efficacy of these instruments gradually eroded and how the writers went about supporting their arguments. As the seventeenth century progressed, chance and patronage were mentioned in the same breath. Securing a patron was viewed as the best guarantee against the vagaries of fate, which ruled an open art market that had been in decline since the third quarter of the century. Achieving success was thus considered to be primarily a social matter too, a conclusion consistent with recent theoretical formation in sociology and network science on the subject of artistic success.
Keywords: Mander, Karel van -- 1548-1606; Hoogstraten, Samuel van -- 1627-1678; Gool, Jan van -- 1685-1763; Houbraken, Arnold -- 1660-1719; Geschichte 1600-1760; Maler; Erfolg; Mobilität; Zufall; Mäzenatentum; Netzwerk; Niederlande